Enhancing the Recovery of Bioactive Compounds of Soybean Fermented with Rhizopus oligosporus Using Supercritical CO2: Antioxidant, Anti-Inflammatory, and Oxidative Proprieties of the Resulting Extract - Fernanda Guilherme do Prado; Maria Giovana Binder Pagnoncelli; Maria Rosa Machado Prado; Marcos Lucio Corazza; Vanete Thomaz Soccol; Gilberto Vinícius de Melo Pereira; Carlos Ricardo Soccol (Journal of Fungi, 2022)
The aim of the present study was to evaluate the use of supercritical CO2 combined with cosolvent for the recovery of bioactive compounds of soybean fermented with Rhizopus oligosporus NRRL 2710. Soxhlet extractions using seven different organic solvents (n-hexane, petroleum ether, ethyl acetate, acetone, ethanol, methanol, and water) were initially performed for comparative purposes. The extracts obtained were characterized by physicochemical, antioxidant, total phenolic, and oxidative proprieties. For the Soxhlet extractions, the highest and lowest yields obtained were 45.24% and 15.56%, using methanol and hexane, respectively. The extraction using supercritical CO2 combined with ethanol as a static modifier (scCO2 + EtOH) presented, at a high pressure (25 MPa) and temperature (80 °C), a phenolic compound content of 1391.9 μg GAE g−1 and scavenging of 0.17 g, reaching a 42.87% yield. The extracts obtained by sCO2 + EtOH were characterized by high contents of essential fatty acids (linoleic acid and oleic acid) and bioactive compounds (gallic acid, trans-cinnamic acid, daidzein, and genistein). These extracts also showed a great potential for inhibiting hyaluronidase enzymes (i.e., anti-inflammatory activity). Thermogravimetric analyses of the samples showed similar profiles, with oil degradation values in the range from 145 to 540 °C, indicating progressive oil decomposition with a mass loss ranging from 93 to 98.7%. In summary, this study demonstrated the flexibility of scCO2 + EtOH as a green technology that can be used to obtain high-value-added products from fermented soybean.